2011
DOI: 10.1007/s00066-011-2226-6
|View full text |Cite
|
Sign up to set email alerts
|

Regionale Hyperthermie kombiniert mit Chemoradiotherapie bei Erstdiagnose oder Rezidiv eines primären oder rezidivierten lokal fortgeschrittenen Pankreaskarzinoms: eine offene Kohortenvergleichsstudie

Abstract: HT can be added safely to CRT in LAPC, thus, resulting in slightly prolonged survival in certain cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
3
34
0
1
Order By: Relevance
“…After the first and second selection (Figure 1), 14 studies were included [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two patient cohorts were each described in two articles; for these we excluded the oldest [67,68] and included the latest [54,57].…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…After the first and second selection (Figure 1), 14 studies were included [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two patient cohorts were each described in two articles; for these we excluded the oldest [67,68] and included the latest [54,57].…”
Section: Literature Searchmentioning
confidence: 99%
“…The included 14 studies combined 395 pancreatic cancer patients of whom 248 received HT (Table 1). Six out of 14 studies used a control population that enabled a comparison between treatments with and without hyperthermia [54,55,57,60,62,66]. In two studies, patients with a variety of carcinomas were included, but data were reported for the pancreatic patients separately [53,59].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…The Italian Trial (Maluta et al 2011) [31] Underlying is a combination treatment of radiation (from 30 Gy/10 fractions to 66 Gy/33 fractions) with chemotherapy (CT). CT consisted of gemcitabine alone or in association with either oxaliplatin, cisplatin or 5-FU.…”
Section: The German Study I (Hager Et Al 2006) [24]mentioning
confidence: 99%